An empirical investigation of adopters' perceptions toward m-commerce: The case of Bulgarian University students - Nora Milanova; Vaggelis Saprikis (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2018)
Mobile commerce (m-commerce) is a fact. Nowadays, numerous transactions take place via mobile devices. At the same time, m-commerce is considered as one of the fastest growing subgroups of e-commerce. Characteristically, it is estimated that about 45% of mobile users have made at least one purchase via a wireless hand-held device. Therefore, it plays and will continue to play a vital role in the global economy. The aim of this research paper is to investigate the perceptions of mobile commerce users focusing on Bulgarian University students. Specifically, it intends to reveal the perceived advantages and disadvantages of m-commerce, the factors that motivate students to make online transactions via a hand-held device, as well as the issues that hinder them from doing so more often. The paper is expected to provide tangible results to both academia and the industry about a developing economy.
Keywords: M15; M39; 650; mobile commerce; m-commerce intention; mobile shopping adoption